The bronze belts of the South Caucasus: through object to context - Manukyan, Sona (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The present paper discusses the archaeological context of the Late Bronze and Iron Age bronze belts of the South Caucasus. The previous studies (19th-20th centuries) were mainly focused on the interpretation of the ornaments and function of the belts, whereas no fundamental and comprehensive study of the context has been done yet, which keeps our understanding of the belts limited. This research aims to fill this gap by conducting cluster analysis of the graves in the necropoleis of Akhtala, Karmir Berd, Mastara, Musi-yeri, Shirakavan, Talin (Republic of Armenia), Beshtasheni, Krasnamayatsk, Narekvavi, Samtavro, Tli (Republic of Georgia), Kalakend, and Kalakend Paradiesfestung (Republic of Azerbaijan).